The Role of Celebrity Endorsement in Fashion Product Purchasing Decisions at Shopee: A Qualitative Review - Gracedelia Jeanywealsny Ngasa; Laurensius Sandrio; Septian Hutagalung; Irna Karina Josephine Kaban (Pusat Penelitian dan Pengabdian Masyarakat Politeknik eLBajo Commodus, 2025)
This study aims to examine the effect of celebrity endorsement on purchasing decisions for fashion products on the Shopee e-commerce platform. The research method used is a qualitative approach with non-probability sampling technique. Data was collected through in-depth interviews with Shopee consumers who have experience buying fashion products endorsed by celebrities. The results showed that celebrity endorsement plays a significant role in attracting consumer attention and building trust in the promoted product, which ultimately increases consumer purchase intention. The relationship between fans and celebrities is a key factor in influencing purchasing preferences and behavior. In addition, Shopee as an e-commerce platform also supports increased sales through various attractive features and promotions. This research provides valuable insights for marketers in developing more effective and consumer-oriented marketing strategies in today's digital era.